2022
DOI: 10.1186/s12879-022-07906-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antimicrobial stewardship on antibiogram, consumption and incidence of multi drug resistance

Abstract: Introduction Antimicrobial stewardship programs are intended to improve patient outcomes, reduce side effects, bacterial resistance, and costs. Thus, it is important to assess their impact on an ongoing basis. We aimed to assess the impact of the antimicrobial stewardship program in two different hospitals which used different program approaches. Methodology This is a retrospective observational study in two private hospitals [4088 patient records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Most studies (79%, 42/53) primarily documented a decrease in antibiotic consumption and an improvement in rational antibiotic use after ASP implementation in hospitals [ 39 , 46 , 62 , 64 , 66 – 69 , 71 , 73 , 76 104 ]. Metrics for evaluating antibiotic consumption included defined daily doses (DDDs) or days of therapy (DOT) per 1,000 patient-days [ 62 64 , 68 , 72 , 77 , 79 81 , 84 86 , 88 , 100 , 104 , 105 ] while some studies used defined daily doses (DDDs) per 100 patient-days or Days of therapy/DOT per 100 patient-days [ 66 , 67 , 76 , 90 , 97 , 102 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies (79%, 42/53) primarily documented a decrease in antibiotic consumption and an improvement in rational antibiotic use after ASP implementation in hospitals [ 39 , 46 , 62 , 64 , 66 – 69 , 71 , 73 , 76 104 ]. Metrics for evaluating antibiotic consumption included defined daily doses (DDDs) or days of therapy (DOT) per 1,000 patient-days [ 62 64 , 68 , 72 , 77 , 79 81 , 84 86 , 88 , 100 , 104 , 105 ] while some studies used defined daily doses (DDDs) per 100 patient-days or Days of therapy/DOT per 100 patient-days [ 66 , 67 , 76 , 90 , 97 , 102 ].…”
Section: Resultsmentioning
confidence: 99%
“…24 Therefore, inappropriate use of antimicrobial drugs may also have contributed to the increased incidence of ESBL-E infections during the COVID-19 epidemic. 25 Using multivariate regression analysis, our study showed that a length of hospitalization ≥ 15 days, having chronic kidney disease, using hormonal drugs or ≥ 1 type of antibacterial drugs, and WBC > 9.5×10^9/L were independent risk factors for ESBL-E infection, whereas COPD was a protective factor. Our study found that COVID-19 is not an independent risk factor for ESBL-E infection.…”
mentioning
confidence: 78%
“…Under the auspices of quality improvement, evaluating adherence to such guidelines can confirm their validity, in addition to informing knowledge translation and implementation strategies. SOTR are disproportionately burdened by antimicrobial resistance, antimicrobial-related adverse events, and healthcare-associated infections 30 , 31 . Local guidelines addressing their unique antimicrobial needs may facilitate appropriate prescribing practices.…”
Section: Discussionmentioning
confidence: 99%